2015
DOI: 10.1016/j.brat.2015.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Can a computerised training paradigm assist people with intellectual disabilities to learn cognitive mediation skills? A randomised experiment

Abstract: Aims:The aim was to examine whether specific skills required for cognitive behavioural therapy (CBT) could be taught using a computerised training paradigm with people who have intellectual disabilities (IDs). Training aimed to improve: a) ability to link pairs of situations and mediating beliefs to emotions, and b) ability to link pairs of situations and emotions to mediating beliefs.Method: Using a single-blind mixed experimental design, sixty-five participants with IDs were randomised to receive either comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
2
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 24 publications
1
26
2
1
Order By: Relevance
“…The findings of both Bruce et al (2010) and Vereenooghe et al (2015) are encouraging and potentially offer a new approach to prepare people with IDs prior to accessing CBT, in addition to adaptations to the content and delivery of CBT itself (Whitehouse, Tudway, Look, & Stenfert-Kroese, 2006). Building on this, the current study developed and evaluated a computerised training programme to help people with IDs learn some of the component skills of CBT: i.e.…”
Section: Suitability For Cbt In Terms Of Cognitive Skillsmentioning
confidence: 92%
See 3 more Smart Citations
“…The findings of both Bruce et al (2010) and Vereenooghe et al (2015) are encouraging and potentially offer a new approach to prepare people with IDs prior to accessing CBT, in addition to adaptations to the content and delivery of CBT itself (Whitehouse, Tudway, Look, & Stenfert-Kroese, 2006). Building on this, the current study developed and evaluated a computerised training programme to help people with IDs learn some of the component skills of CBT: i.e.…”
Section: Suitability For Cbt In Terms Of Cognitive Skillsmentioning
confidence: 92%
“…Most of the above studies reported a significant correlation between cognitive mediation ability and level of verbal comprehension, but it is important to bear in mind that participants with limited verbal skills were excluded from these studies. More recently, Vereenooghe, Reynolds, Gega, and Langdon (2015) did not employ exclusion criteria based on verbal skills, but reported substantially higher pass-rates on these tasks using an adapted and computerised version of the tasks.…”
Section: Suitability For Cbt In Terms Of Cognitive Skillsmentioning
confidence: 99%
See 2 more Smart Citations
“…Brief computerised training programmes may improve the ability of people with mild to moderate ID to gain some of the basic skills to engage in cognitive behaviour therapy (CBT; Vereenooghe, Gega, Reynolds, & Langdon, 2016;Vereenooghe, Reynolds, Gega, & Langdon, 2015). This is important because CBT has the potential to reduce anger problems and depression in people with ID (Vereenooghe & Langdon, 2013) but its underlying theoretical rationale is difficult to grasp (Dagnan, Mellor, & Jefferson, 2009;Joyce, Globe, & Moody, 2006;Oathamshaw & Haddock, 2006;Reed & Clements, 1989).…”
Section: Introductionmentioning
confidence: 99%